AN ANALYSIS OF THE ROLE OF CIVIL CONFLICTS IN THE ECONOMIC DEVELOPMENT OF STATES: THE CASE OF UGANDA AND SUDAN (SOUTH SUDAN) - Scholastica Zee Awah (Graduate School of International Studies Ajou University, 2014)
ABSTRACT This research critically looks into the reasons responsible for the divergent economic outcome of civil conflicts on the economies of conflict and post-conflict states of sub-Saharan Africa. Contrary to common placed and popularly upheld thesis that civil wars deter economic growth and development, this piece of research identifies some conflict and post-conflict states in sub-Saharan Africa where in the aftermath of civil conflicts and civil wars specifically did set in place a foundation for and ushered in a period of significant economic growth and reduction in poverty levels. With this opposing thesis, the research work sought at answering two pertinent questions first, if civil conflicts can possibly improve development prospects by creating long term conditions conducive for rapid growth and second, why have some conflict and post-conflict states succeeded in achieving growth and development while others have only experienced economic stagnation or decline. Using the case study of two sub-Saharan African countries, this piece briefs on the recent political-economy of South Sudan (previously a part of Sudan) and Uganda. Limiting its scope to the years after independence to present, the research traces the conflict years in both states and the economy of both states showing the divergent outcome of the wars during and after the conflicts on the economic levels of both states. Using established determinants of the causes of the war, the geographical location of the war, the severity of the war and foreign post-conflict intervention a further section of this research analyzes why some sub-Saharan African states continued to grow during and after the war years where as others declined or stagnated economically and on some instances, fell into recurrent wars.
학위논문(석사)--아주대학교 국제대학원 :국제개발협력과,2014. 8
Keywords: Civil conflicts; Economic development